Pelaksanaan Asimilasi Pada Rumah Tahanan Negara Kelas I Pekanbaru : Pelaksanaan Asimilasi Pada Rumah Tahanan Negara Kelas I Pekanbaru - Wasiah Sufi; Siti Rahayu (Jurnal Karya Ilmiah Multidisiplin (JURKIM), 2022)
This study aims to find out how the implementation of assimilation in the context of preventing the spread of Covid-19 in the Pekanbaru Class I Prison in Pekanbaru and what are the factors that hinder it. The theory used in this research is the implementation theory according to Mazmanian & Sabatier in the Public Policy Book which divides the policy implementation process into three variables, namely Independent Variables (Easy or not the problem is controlled), Intervening Variables (the ability of policies to structure the implementation process), and Dependent Variables. (Stage in the implementation process). The method used in this research is descriptive qualitative with the aim of describing or describing the actual situation. The results of this study are that the implementation of assimilation in the context of preventing the spread of Covid-19 in the Class I Pekanbaru State Detention Center has gone quite well, but in order to achieve the goal effectively and efficiently, implementing officers need to be added and guarantors for prisoners who will be proposed in granting rights. assimilation at home is more prepared so that for prisoners whose rights have been proposed, there will be no cancellation of the granting of assimilation at home due to the absence of their guarantor.